Migration of Sea Turtles - Troëng, Sebastian (2004)
The geographic separation of sea turtle foraging, refu-ge and reproductive habitats makes them undertake extensive migrations. To study this phenomenon, ge-netic analysis, tagging and telemetry have been used, and it has been shown that they can swim hundreds or even thousands of kilometers between nesting bea-ches and foraging habitats and vice versa. Green and hawksbill turtles move towards benthic ha-bitats, where sea grass and sponges grow; while olive ridleys and leatherback turtles migrate to larger and more variable foraging grounds. Currents, eddies and oceanic fronts can influence migrations. Sea turtle sur-vival depend in large measures on the management given to the nesting beaches and surroundings. More resources are needed to improve protection within Costa Rica, and thereby provide an example for other countries, so that when Costa Rican sea turtles pass through their waters, they will help in their protection.